Antique Motifs in Family Subjects of Russian Portraiture in mid-18th — Early 19th Century - Kolmogorova, Ekaterina E. (Actual Problems of Theory and History of Art, 2015)
The article considers antique reminiscences in Russian family portraiture of the 1750s – early 19th century. Benevolence, veneration of ancestors, and love to people around as presented in sentimental literature and painting of this period formed a general concept of “happy family”. Painters used to portray an entire family, or mother and child, or a virtuous spouse surrounded by allegorical environment with symbols of fertility, hearth, and fidelity known from Classical antiquity. Representation of a missing or an untimely deceased relative, or a beloved one as a sublime ideal also served to refer to ancient tradition implied in busts, sculpted medallions, and cameos. Tendency to present “antique” air as a model of inartificial mode of life was also evident in costumes and accessories. Thus it can be concluded that antique motifs are traced in composition, narration, style and symbolism of Russian family portraiture of 1750s – early 19th century.
Keywords: antique motifs; allegory; 18th century Russian painting; 18th century Russian culture; family portrait; family representation; group portrait; miniature; sculptural portrait